Effectiveness of Psychotherapy in Adult ADHD: What Do Patients Think? Results of the COMPAS Study. Issue 9 (July 2019) - Groß, Vivien; Lücke, Caroline; Graf, Erika; Lam, Alexandra P.; Matthies, Swantje; Borel, Patricia; Sobanski, Esther; Rösler, Michael; Retz, Wolfgang; Jacob, Christian; Colla, Michael; Huss, Michael; et al.
Objective: In the multicenter study Comparison of Methylphenidate and Psychotherapy in Adult ADHD (COMPAS), the efficacy of treatments has been primarily evaluated by observer-rated symptom change. Here, we additionally analyzed the patients' subjective evaluation of therapy effects.Method: COMPAS compared ADHD-specific group therapy with unspecific clinical management with/without concomitant pharmacotherapy in a four-armed design. Evaluation through the patients' retrospective perspective was performed after 1 year (post-treatment) and after another 1.5 years (follow-up).Results: In respect to patients' subjective ratings, ADHD-specific group psychotherapy outperformed unspecific management post-treatment ( z = 4.88, p < .0001) and at follow-up ( z = 2.90, p = .004). Rank correlations with rater-based symptom change were small to moderate (post-treatment: r s = 0.28, follow-up: r s = 0.16).Conclusion: Therapy evaluation based on the patients' perspective supports the concept of ADHD-specific group psychotherapy as a potentially useful therapy option in ADHD.